Piston ventilation modulates thermal comfort in subway hubs via a dual-path coupling mechanism: A field study in Nanjing, China - Yuxuan Liu; Jiawei Leng; Yueming Wen; Haifei Zhou; Deqing Lin; Yuchong Qian (Building and Environment, 2026)

Intelligent aeration technologies in grain storage: A comprehensive review of multi-physics modeling and AI-driven control - Xiaoyu Zhang; Jiale Guo; Yanhong Liu; Yuanyi Luo; Shuanglin Wang; Deqing Wang; Jie Lin; Kun Hu; Haoyu Wen; Yining Wu; Xiaoping Yan (Journal of Stored Products Research, 2026)

Nonlinear effects of urban morphology on the thermal environment in the Jinan ancient city: An explainable machine learning approach - Chang Xu; Wei Xue; Deqing Lin; Xiaodong Xu (Urban Climate, 2026)

Field validation of a multi-functional dry habitat for subsea pipeline maintenance - Jin Guo; Jiawang Chen; Bo Han; Haiyang You; Yuan Lin; Deqing Mei (Ocean Engineering, 2026)

Numerical simulation of thruster-thruster interaction and optimization of thrust performance for ROVs with vector layout propulsion systems - Jin Guo; Jiawang Chen; Peiwen Lin; Zhangyong Jin; Deqing Mei (Ocean Engineering, 2026)

Integrating stimulation and CO2 storage in natural gas hydrate reservoirs: visualization of CO2-foam fracturing and hydrate self-sealing - Kunlin Ma; Jingsheng Lu; Zhibin Sha; Dongliang Li; Decai Lin; Xiaoya Zang; Deqing Liang (Journal of Cleaner Production, 2026)

Exploring efficient mainstream nitrogen removal by partial nitrification/anammox under limited COD condition in a pilot-scale membrane aerated biofilm reactor - Lisheng Wang; Congcong Zhang; Xiaofeng Kang; Yanchen Liu; Yong Qiu; Deqing Wanyan; Jiayin Liu; Gang Cheng; Pengfei Lin; Xia Huang (Water Research, 2026)

A scalable and efficient framework for city-scale building energy modeling with microclimate considerations - Ke Liu; Xiaodong Xu; Deqing Lin; Ran Zhang; Linzhi Zhao; Abudureheman Abuduwayiti; Francesco Causone (Sustainable Cities and Society, 2026)

Searching for neutrinoless double-beta decay of 136 Xe with PandaX-4T - Shu Zhang; Zihao Bo; Wei Chen; Xun Chen; Yunhua Chen; Zhaokan Cheng; Xiangyi Cui; Yingjie Fan; Deqing Fang; Zhixing Gao; Lisheng Geng; Karl Giboni; et al. (Science Bulletin, 2025)

Interpretable data-driven urban building energy modeling considering inter-building effect - Deqing Lin; Xiaodong Xu; Ke Liu; Tingjin Wu; Xi Wang; Ran Zhang (Building and Environment, 2025)

Achieving mainstream nitrogen removal by partial nitrification and anammox in the carriers-coupled membrane aerated biofilm reactor - Lisheng Wang; Congcong Zhang; Yanchen Liu; Yong Qiu; Deqing Wanyan; Jiayin Liu; Gang Cheng; Pengfei Lin; Xia Huang (Water Research, 2025)

Antennal transcriptome analysis of Psyttalia incisi (silvestri) (Hymenoptera: Braconidae): identification and tissue expression profiling of candidate odorant-binding protein genes - Deqing Yang; Dongliang Li; Lili Jiang; Jia Lin; Guoqing Yue; Kang Xiao; Xuxing Hao; Qinge Ji; Yongcong Hong; Pumo Cai; Jianquan Yang (Molecular Biology Reports, 2024)

Establishing Virtual Bioequivalence and Clinically Relevant Specifications for Omeprazole Enteric-Coated Capsules by Incorporating Dissolution Data in PBPK Modeling - Ruwei Yang; Yaqi Lin; Kaifeng Chen; Jie Huang; Shuang Yang; An Yao; Xiaoyan Yang; Deqing Lei; Jing Xiao; Guoping Yang; Qi Pei (The AAPS Journal, 2024)

Effects of low-concentration spinetoram wax-based bait stations on Bactrocera dorsalis (Diptera: Tephritidae) - Jia Lin; Guoqing Yue; Kang Xiao; Deqing Yang; Xuxing Hao; Minlin Zheng; Pumo Cai; Qing'e Ji (Pesticide Biochemistry and Physiology, 2023)

Microcosmic Characteristics of Hydrate Formation and Decomposition in the Different Particle Size Sediments Captured by Cryo-SEM - Jingsheng Lu; Decai Lin; Dongliang Li; Deqing Liang; Long Wen; Siting Wu; Yiqun Zhang; Yong He; Lingli Shi; Youming Xiong (Journal of Marine Science and Engineering, 2022)
Sand production and sand control studies in non-diagenetic reservoirs are the weak point in the conventional petroleum industry. However, natural gas hydrate (NGH) mainly exists in non-diagenetic strata, and sand production occurs during exploitation, which restricts the safe and sustainable production of NGH. To study the microcosmic characteristics of sand production, the hydrate decomposition behaviours in the sediments were captured by the Cryo-SEM method. The micromorphology of different particle sizes of sand samples containing NGH (the sand median diameter d50 is 150, 87, 55, 38, 24, and 13 µm) and the microcosmic processes of NGH decomposition were observed. Then, the microcosmic characteristics of sand production, during the decomposition process, were analysed. (1) The gas hydrate decomposition increases pore space and reduces reservoir strength; the expansion action of the decomposition of water and gas, the softening action of the decomposition of water, and the compression action by overlying stress (crustal stress) promoted sand production, deformation, and subsidence of the NGH reservoirs in the mining process. (2) The decomposition of NGH has a more significant impact on sediments with smaller particle sizes. (3) The particle size of NGH may be larger than the particle size of the mud in the reservoirs, and acting as “gravel” plays a particular role in sand control. Therefore, the particle size of NGH cannot be ignored in the design of sand control. (4) It has been revealed, and verified, that sputtering (splashing) is a unique process of sand production caused by NGH decomposition. In other words, the rapid expansion of the volume of the decomposed gas and water from NGH leads to the eruption and sputtering of hydrate particles, providing the driving force for sand migration, which is a different process of sand production than in conventional oil and gas.

PTEN-mediated mitophagy and APE1 overexpression protects against cardiac hypoxia/reoxygenation injury - Wenshuai Tang; Deqing Lin; Mingxiang Chen; Zhiping Li; Weimin Zhang; Wenping Hu; Fuping Li (In Vitro Cellular & Developmental Biology - Animal, 2019)

An efficient method of noroviruses recovery from oysters and clams - Deqing Zhou; Liping Ma; Feng Zhao; Lin Yao; Laijin Su; Xinguang Li (Journal of Ocean University of China, 2013)